2018
DOI: 10.1523/eneuro.0204-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic Study of Anterior BNST and Basomedial Amygdala Projections to the Ventromedial Hypothalamus

Abstract: The basomedial amygdala (BM) influences the ventromedial nucleus of the hypothalamus (VMH) through direct glutamatergic projections as well as indirectly, through the anterior part of the bed nucleus of the stria terminalis (BNSTa). However, BM and BNSTa axons end in a segregated fashion in VMH. BM projects to the core of VMH, where VMH’s projection cells are located, whereas BNSTa projects to the shell of VMH, where GABAergic cells that inhibit core neurons are concentrated. However, the consequences of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 56 publications
5
33
0
Order By: Relevance
“…In this way, afferents from the entorhinal cortex to the CA3 neurons (Neves et al, 2008) remained functional in acute slices. We also confirmed the presence of entorhinal cortex-hippocampal afferents in acute slices utilizing tracing experiments (Tervo et al, 2016;Yamamoto et al, 2018) and dual recordings from entorhinal cortex and CA3 area. These data are in line with another publication demonstrating the presence of intact entorhinal cortex to hippocampus afferents in the str.…”
Section: Transfection Of Hippocampal Neurons With Gcamp6ssupporting
confidence: 67%
“…In this way, afferents from the entorhinal cortex to the CA3 neurons (Neves et al, 2008) remained functional in acute slices. We also confirmed the presence of entorhinal cortex-hippocampal afferents in acute slices utilizing tracing experiments (Tervo et al, 2016;Yamamoto et al, 2018) and dual recordings from entorhinal cortex and CA3 area. These data are in line with another publication demonstrating the presence of intact entorhinal cortex to hippocampus afferents in the str.…”
Section: Transfection Of Hippocampal Neurons With Gcamp6ssupporting
confidence: 67%
“…As a result, the HPA axis response is elicited. The BLA activation is simultaneously transmitted to the basomedial nucleus of the amygdala [26] and then to the VMH [48]. The VMH activation is further transmitted to the anterior hypothalamus [46] and induces avoidance behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrated that the two classes of MePD inhibitory neurons in males received predominant excitatory inputs. Previous studies have shown that MePD neurons project to the BNST, the main efferent pathway in males (de Olmos et al, 2004;Pardo-Bellver et al, 2012), containing mostly GABAergic cells (Poulin et al, 2009;Yamamoto et al, 2018) and projecting to the hypothalamus (Dong et al, 2001). Therefore, the MePD neurons could disinhibit the hypothalamic cells via an indirect pathway, by inhibiting BNST GABAergic cells.…”
Section: Working Hypothesis For Sex and Cycle Estrous-related Differementioning
confidence: 99%